The leadership pipeline : how to build the leadership powered company - Charan, Ram; Drotter, Stephen J.; Noel, James L., 1943- (San Francisco : Jossey-Bass, 2011)
'In business, leadership at every level is a requisite for company survival. Yet the leadership pipeline -- the internal strategy to grow leaders -- in many companies is dry or nonexistent. Drawing on their experiences at many Fortune 500 companies, the authors show how organizations can develop leadership at every level by identifying future leaders, assessing their corporate confidence, planning their development, and measuring their results. They integrate the leadership development process with a succession planning process for a proven system that enables companies to constantly renew their pipeline without having to overspend for outside talent. Their comprehensive breakdown of the six primary leadership transitions in the pipeline apply to almost any company structure. The new edition will have a new foreword and preface;chapters will each have new'Observations from the Field Sections' with updates to the model, new stories and additional advice and a'Frequently Asked Questions' section. In sum they have added 25% new material.'--Provided by publisher.
Includes index.
Keywords: Leadership; Industrial management; Leadership; Industrial management